2022
DOI: 10.3390/mi13050643
|View full text |Cite
|
Sign up to set email alerts
|

Schistoscope: An Automated Microscope with Artificial Intelligence for Detection of Schistosoma haematobium Eggs in Resource-Limited Settings

Abstract: For many parasitic diseases, the microscopic examination of clinical samples such as urine and stool still serves as the diagnostic reference standard, primarily because microscopes are accessible and cost-effective. However, conventional microscopy is laborious, requires highly skilled personnel, and is highly subjective. Requirements for skilled operators, coupled with the cost and maintenance needs of the microscopes, which is hardly done in endemic countries, presents grossly limited access to the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 26 publications
(33 reference statements)
1
38
0
Order By: Relevance
“…The Schistoscope 5.0 ( Figure 1 ) is a low-cost automated slide-scanner digital microscope that can be supported with AI algorithms for image processing. 18 The system is composed of custom-designed optical bright-field illumination, three-axis movement (X, Y, Z), and electronic and computing modules. The illumination module comprises a bright white light-emitting diode and condenser lenses to generate uniform illumination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Schistoscope 5.0 ( Figure 1 ) is a low-cost automated slide-scanner digital microscope that can be supported with AI algorithms for image processing. 18 The system is composed of custom-designed optical bright-field illumination, three-axis movement (X, Y, Z), and electronic and computing modules. The illumination module comprises a bright white light-emitting diode and condenser lenses to generate uniform illumination.…”
Section: Methodsmentioning
confidence: 99%
“…The on-board computer is a Raspberry Pi 4B connected to a Raspberry Pi HQ camera that has a pixel size of 1.55 µm and an image resolution of 2028 × 1520 pixels. The current study used a 4× microscope objective that provides an experimental resolution limit of 3.26 μm, 18 which is sufficient to resolve S. haematobium eggs ( Figure 1C ). The device runs on mains electricity and does not have a built-in battery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycerine or mounting medium may be added to the egg containing filter membranes on a glass slide, allowing later examination. Hence this equipment should not be limited to KK for STH and S. mansoni but should include filtration technique for S. haematobium too (54,55). The capability of the AI component introduces the multiplexing capacity within the same sample for each determinant that it has been trained with.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 8 non-smartphone-based optical devices reviewed here, six were limited to proof-of-concept (Linder et al, 2013;Holmstrom et al, 2017;Sukas et al, 2019;Agbana et al, 2020;Dacal et al, 2021;Oyibo et al, 2022) as reported by the authors. The first study by Linder et al demonstrated the use of a mini-microscope (On-Chip) to image and detect the eggs of S. haematobium with AI (Linder et al, 2013).…”
Section: Non-smartphone-based Optical Devicesmentioning
confidence: 99%